Implementasi Manajemen Pendidikan Islam di Pondok Pesantren - Yayat Supriyadi; Tihami Tihami; Agus Gunawan (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2023)
Since the 16th century, Pesantren, the oldest educational institution in Indonesia, has been operating. It will continue to grow until it is recognised as a key player in the nation's education. Many individuals and leaders who made Indonesia proud and contributed significantly to Indonesia's independence were born in Pesantren. Pesantren has a very important role in improving the intelligence of the nation's generation, especially in the current era of globalisation. In accordance with the demands of the times, pesantren must be able to make various improvements in various fields, especially in the management of student services and the learning and management process of pesantren that do not only rely on figures, but have a learning and governance system that touches the implementation of professional management so that the management of all elements in the pesantren can develop better. Through the implementation of professional management, boarding schools are expected to contribute to developing individuals who are intelligent, moral, and spiritually strong and can utilise various technical advances and expertise for themselves and society. This research is descriptive qualitative, which is research whose results are written in the form of a series of narratives, not in the form of numbers, but supported by library research.